Potentially suitable areas for Ricania speculum (Hemiptera: Ricaniidae) in China under climate change - Feng, Xueli; Zhao, Zhengxue; Wang, Yingjian; Zhang, Yubo (Frontiers in Ecology and Evolution, 2025)
Determining the suitable areas for pests and the dynamic shift of these areas under climate change is crucial for their management and control. The black planthopper (Ricania speculum) is an economically important pest in China, but knowledge about the suitable areas for its habitation is limited. Therefore, in this study, a Maxent model was constructed using 111 occurrence records and related environmental variables to predict the suitable areas for it to inhabit now and in the future (2041–2060, 2061–2080, and 2081–2100) in China, following by exploration of their dynamic shift. The model results showed that the currently suitable areas are predominantly in central and southern provinces such as Henan, Anhui, Hubei, and Guizhou, while the areas that are highly suitable are the most abundant among the three levels of suitability. Furthermore, the number of suitable areas for R. speculum in the three future periods was predicted to increase compared with that in the current period; the results also revealed that the suitable areas for R. speculum will consistently expand northward. The results of this study deepen our understanding of the impacts of climate change on the distribution of R. speculum and should also be beneficial for farmers and government departments to develop appropriate and cost-effective pest management strategies to reduce economic damage to China’s agricultural systems.